ON THE SUPPOSED CONNECTION BETWEEN ARISTOTLE'S METAPHYSICS AND LOGIC. - Boongaling, John Ian K. (Problems / Problemos, 2018)
This paper investigates a particular strategy for establishing the deep connection between metaphysics and logic using Aristotle's principle of non-contradiction and the theory of predication. The decisive move, according to this strategy, is to formulate and interpret the said principle as a metaphysical (or ontological) principle. In this paper, it is argued that: (1) despite the strategy's initial appeal, a successful argument still needs to be made in order to fully establish that metaphysics and logic are deeply connected, and (2) the theory of predication is more fundamental than the principle of non-contradiction. The main reason for (1) above is that the strategy is prone to a very powerful objection that Aristotle's criterion of primary substance is inconsistent. The main reason for (2) above is that the principle of non-contradiction itself is best explained using the theory of predication. In addition, it is the theory of predication that does all the important explanatory work in the context of Aristotle's philosophical theory.